DOUBLE MECKEL'S DIVERTICULUM PRESENTING AS ACUTE APPENDICITIS: A CASE - Emre, A; Akbulut, S; Yilmaz, M; Kanlioz, M; Aydin, BE (2013)
Background: Meckel's diverticulum is the most common developmental anomaly of the gastrointestinal tract, affecting 1-3% of the general population. This anomaly is caused by incomplete obliteration of the omphalomesenteric duct during the 7th week of gestation and is located in the last meter of the ileum in 90% of patients. Meckel's diverticulumis often an incidental finding during a laparotomy for other causes, such as acute appendicitis, and occasional complications are bleeding, obstruction, diverticulitis, and perforation. Objective: Primary aim of this study was to present and share an extremely rare case of double Meckel's diverticulum. Methods: A 20-year-old woman who was admitted due to symptoms of right lower quadrant pain, nausea, and vomiting. A laparotomy with a McBurney's incision was performed because of a presumed diagnosis of acute appendicitis. The surgical exploration revealed a double Meckel's diverticulum localized 50 cm proximal to the ileocecal valve, but no acute appendicitis. The operation was finished after a diverticulectomy and appendectomy. No complications occurred during the postoperative follow-up. Conclusions: We conducted a literature review of studies published in the English language on double Meckel's diverticulum, accessed via PubMed, Medline, and the Google Scholar databases. We found only five case reports of such a Meckel's diverticulum variant. (C) 2013 Elsevier Inc. C1 [Emre, Arif; Kanlioz, Murat] Malatya State Hosp, Dept Surg, Malatya, Turkey. [Akbulut, Sami; Yilmaz, Mehmet] Inonu Univ, Fac Med, Dept Surg, Div Liver Transplantat, TR-44280 Malatya, Turkey. [Aydin, Burcu Elif] Malatya State Hosp, Dept Pathol, Malatya, Turkey.